Teacher training in early childhood education: contemporary challenges for continuing training - Marianne Manhães Fernandes; Carla Quintanilha Corrêa (Universidade Federal de Santa Catarina, 2014)
This article discusses the ongoing training of early childhood teachers in Brazil. For this, the existing features in the quality of initial and continuing teachers of the first stage of basic education training difficulties, highlighting the main challenges faced by these professionals. Through field research conducted with the participation of one hundred (100) teachers from kindergarten of Goytacazes/RJ/Brazil, there was the difficulty experienced by teachers with regard to the quality of both initial training they received, as the continuing education that has been offered by the government. Thus, the objective is to generate reflection on what should be done by the authorities, especially regarding the need for investment in this area, encouraging continuous professional development, seeking quality education, enabling the acquisition of new knowledge and skills to meet fully the specificities of the child. Keywords: Childhood Education; Continuing Education; Educational Quality